2018
DOI: 10.1021/acssynbio.8b00126
|View full text |Cite
|
Sign up to set email alerts
|

Optical Activation of TrkA Signaling

Abstract: Nerve growth factor/tropomyosin receptor kinase A (NGF/TrkA) signaling plays a key role in neuronal development, function, survival, and growth. The pathway is implicated in neurodegenerative disorders including Alzheimer's disease, chronic pain, inflammation, and cancer. NGF binds the extracellular domain of TrkA, leading to the activation of the receptor's intracellular kinase domain. As TrkA signaling is highly dynamic, mechanistic studies would benefit from a tool with high spatial and temporal resolution.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 58 publications
(102 reference statements)
3
37
0
Order By: Relevance
“…Particularly, we found that CRY2-based Opto-iTrkB + CIBN-CAAX is the most effective strategy to activate TrkB receptors by quantifying the degrees of PC12 neurite outgrowth and comparing the levels of phosphorylated ERK and Akt. The result agrees with our previous report that the same design for TrkA receptors, Opto-iTrkA + CIBN-CAAX, can activate TrkA signaling better than other methods exploiting full-length receptors or membrane-bound intracellular domain of the receptors [24]. To further improve the activation efficiency in the future, CRY2 variants with enhanced homo-interacting abilities, such as CRY2high [41], CRY2clust [42] or CRY2oligo [43], can be incorporated into the Opto-iTrkB + CIBN-CAAX construct.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Particularly, we found that CRY2-based Opto-iTrkB + CIBN-CAAX is the most effective strategy to activate TrkB receptors by quantifying the degrees of PC12 neurite outgrowth and comparing the levels of phosphorylated ERK and Akt. The result agrees with our previous report that the same design for TrkA receptors, Opto-iTrkA + CIBN-CAAX, can activate TrkA signaling better than other methods exploiting full-length receptors or membrane-bound intracellular domain of the receptors [24]. To further improve the activation efficiency in the future, CRY2 variants with enhanced homo-interacting abilities, such as CRY2high [41], CRY2clust [42] or CRY2oligo [43], can be incorporated into the Opto-iTrkB + CIBN-CAAX construct.…”
Section: Discussionsupporting
confidence: 92%
“…Lyn-iTrkB-mCh-CRY2: The intracellular domain of TrkB (a.a. 455-822) was inserted into our previous construct Lyn-iTrkA-mCh-CRY2 [24] at SacI and BsrGI sites using In-Fusion (Clontech).…”
Section: Plasmid Cloningmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group and others have successfully leveraged the Arabidopsis thaliana photoreceptor CRY2 3 to make light-inducible constructs of several RTKs, including FGFR 4,5 , EphB2 6 , and the neurotrophin receptors TrkA, TrkB, and TrkC [7][8][9] . The blue light-induced clustering of CRY2 lends itself especially well to reproducing the conditions for RTK activation.…”
Section: Introductionmentioning
confidence: 99%